"Artificial control environment" methodology: theoretical justification and test solutions - Vypasniak, Ihor; Fedyniak , Nazarii (Journal of Education, Health and Sport, 2020)
Relevance. The methodology of the "artificial control environment" consists of forming a complex of special conditions during human physical exercise. This approach is aimed at targeted correction, management and development of motor patterns. The main characteristics of such an environment are its controllability, focus on specific tasks and dynamism. Research tasks. To study the current state of the problem under study, to generalize domestic and international experience in using the methodology of "artificial control environment" in the process of physical exercise. To accomplish the tasks set, an analysis of scientific and methodological literature, pedagogical research methods were used. Research results. A. M. Laputin is recognized as the founder of the scientific paradigm of the "artificial control environment" in physical culture and sports. His contribution lies in the development of a methodological basis, conceptual apparatus and key principles. The central idea, empirically proven in his research and followers, is the dependence of the quality and nature of motor activity on the parameters of the external environment. This conceptual position substantiates the need to use an "artificial control environment" to achieve the goals of correctional and preventive activities. Conclusions. In world practice, similar ideas are being studied under the names of "technologically assisted physical activity" and "immersive fitness environments". The main areas of such research are the use of: robotics for rehabilitation; VR games for physical and cognitive therapy of the elderly; mobile platforms that create a gaming environment for home workouts. Further scientific research will be aimed at developing and implementing the means and methods of "artificial control environment" in the system of health fitness classes for women in the second period of mature age in order to increase their effectiveness.